Analyzing the drone debates targeted killing, remote warfare, and military technology - Rae, James DeShaw (Palgrave pivot, 2014)
The book examines principal arguments for and against the use of unmanned aerial vehicles for surveillance and 'targeted killing.' Addressing both sides of the argument with clear and cogent details, the book provides a thorough introduction to ongoing debate about the future of warfare and its ethical implications.